Analisa Faktor-Faktor Penerimaan Pajak Hiburan di Kota Batu - Iranti Ratna Susanto (Jurnal Ilmiah Mahasiswa FEB, 2015)
Entertainment tax is one of the largest revenue of District Own Source Revenue in Batu city, considering that Batu city is a tourist town that has great potential in entertainment tax revenue. This study aims to determine how much influence factors of entertainment tax revenue that is the amount of entertainment tax object, the number of visitors, the number of residents, receipt of incentives by Dispenda Batu City and tourism sector GDP to tax revenues entertainment in Batu City. Data were obtained through interviews, questionnaires, documentation and literature study. By using multiple linear regression with time series data using SPSS 20, the results showed that the number of objects entertainment tax, the number of visitors, the number of residents, receipt of incentives Dispenda and tourism sector GDP has a significant positive effect on the acceptance of entertainment tax in Batu City. Keywords: Entertainment tax, District Own Resources Revenue, Factors of entertainment tax revenue